Enhancement of neuroprotective activity of Sagunja-tang by fermentation with lactobacillus strains - Nam-Hui Yim; Min Jung Gu; Hee Ra Park; Youn-Hwan Hwang; Jin Yeul Ma (BMC, 2018)
Abstract Background Sagunja-tang (SGT) is widely used in traditional herbal medicine to treat immune system and gastrointestinal disorders and reportedly has protective effects against inflammation, cancer, and osteoporosis. In this study, we fermented SGT with different Latobacillus strains and investigated the change in phytochemical compositions in SGT and enhancement of it neuroprotective effects in SH-SY5Y human neuroblastoma. Methods Marker components, including ginsenoside Rg1, glycyrrhizin, liquiritin, liquiritigenin, atractylenolide I, atractylenolide II, atractylenolide III, and pachymic acid, in SGT, were qualitatively and quantitatively analyzed using high-performance liquid chromatography-diode array detection and liquid chromatography-mass spectrometry. SGT was fermented with eight different Lactobacillus strains to yield eight fermented SGTs (FSGTs). The conversion efficiencies of SGT marker components were determined in each FSGT. To detect the protective effect of SGT and FSGT, reactive oxygen species (ROS) assay and mitochondrial membrane potentials (MMPs) assay were performed in SH-SY5Y cells. Results Compared with the other FSGTs, SGT166, i.e., SGT fermented with L. plantarum 166, had high conversion efficiency, as indicated by increased amounts of glycyrrhizin, liquiritigenin, and atractylenolides I-III. In SH-SY5Y cells, protection against cell death induced by H2O2 and etoposide was high using SGT166 and very low using SGT. Furthermore, ROS production and mitochondrial membrane potential disruption in SH-SY5Y cells were markedly suppressed by SGT166 treatment, which demonstrated that inhibition of ROS generation may be one of the neuroprotective mechanisms of SGT166. Conclusions This study demonstrated that fermentation of SGT with L. plantarum 166 enhanced suppression of oxidative stress and MMP loss. This enhanced neuroprotective effect was thought to be caused by the conversion of SGT phytochemicals by fermentation. SGT166 shows potential for treating neurological damage-related diseases.